Exploring the Adaptability of Foreign Special Education Teachers Working with Students with Special Needs in Columbia South Carolina - Bautista, Neil Arvin V.; De Castro, Luningning B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
Foreign teachers of students with special needs undergo the process of adaptation as they face different work dynamics. This phenomenological study aimed to explore the experiences of adaptation among foreign teachers in teaching learners with disabilities in South Carolina. Seven (7) foreign Special Education teachers teaching in South Carolina, who have participated in the interviews. Through thematic analysis, the study revealed themes to describe their lived experiences, views in working in the Special Education setting in South Carolina, and their adaptation to work. In terms of lived experiences, teachers described their experiences with themes such as: journeying through emotional and reflective realities of teaching; relationship building and collaboration; managing institutional demands and complex student needs; and adapting instruction and demonstrating pedagogical creativity. Foreign Special Education teachers viewed themselves of having global perspectives contribute to enriching the school community; and play the role of being the builder of inclusive, trusting, and culturally responsive educational spaces were also highlighted in the study. Findings also reveal that teachers adapt through instructional and professional adaptation; relational and collegial adaptation; and cultural integration and adjustment as ways on how they adapt to the teaching environment in the USA. The essence of foreign Special Education teachers’ experiences is captured by resilience, ongoing process of transformation, adaptation, and cultural integration, highlighting their critical role in enriching inclusive school environments. These findings highlight the need for culturally responsive training, supportive leadership, and inclusive policies to empower foreign Special Education teachers in U.S. classrooms.